2018
DOI: 10.1007/s11695-018-3336-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Nutrition Data in Terms of Vitamin D, Vitamin B12, and Albumin After Bariatric Surgery and Long-term Fracture Data Compared with Conservatively Treated Obese Patients: a Retrospective Cohort Study

Abstract: Vitamin 25(OH)D, B12, and albumin levels were mainly within recommended levels during the 2 years after bariatric surgery. The cumulative fracture risk was higher in bariatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
3
14
1
Order By: Relevance
“…These divergent results might be partly explained by different reference values and surgical procedures performed. The present data is in line with a report by Javanainen et al who observed a prevalence of vitamin B 12 deficiency in 1 to 3% of patients 2 years after bariatric surgery when using a comparable reference value (138 pmol/l) [25].…”
Section: Discussionsupporting
confidence: 93%
“…These divergent results might be partly explained by different reference values and surgical procedures performed. The present data is in line with a report by Javanainen et al who observed a prevalence of vitamin B 12 deficiency in 1 to 3% of patients 2 years after bariatric surgery when using a comparable reference value (138 pmol/l) [25].…”
Section: Discussionsupporting
confidence: 93%
“…The authors also found that calcium and vitamin D supplementation was independent of fracture risk after gastric bypass surgery, which is in agreement with recent data showing that vitamin D status after bariatric surgery was not a risk factor for fractures . Indeed, these findings are compatible with results from a prospective study including obese premenopausal women with either type of bariatric surgery, sleeve gastrectomy or Roux‐en‐Y gastric bypass, that the latter type caused significantly larger bone loss in the femoral neck, but not the lumbar spine, compared with the former type as expected, whereas both types markedly and similarly reduced calcium absorption in the gut .…”
supporting
confidence: 88%
“…Sugiyama further concludes that our results agree with a recent study reporting that vitamin D status was not a predictor of fracture in patients who had undergone gastric bypass surgery . We do not believe that the study by Javanainen and colleagues is particularly strong in terms of finding determinants of fracture risk because the power in the analysis was rather insufficient, with only 31 fractures in the RYGB group and 17 among the controls.…”
supporting
confidence: 86%